Glycyrrhizin and Omega-3 fatty acids have hepatoprotective roles through toll-like receptor-4. Issue 1 (2nd January 2019) - Abo El-Magd, Nada F.; El-Karef, Amro; El-Shishtawy, Mamdouh M.; Eissa, Laila A.
ABSTRACT: This study investigated the hepatoprotective role of natural compounds [glycyrrhizin (GL) and omega-3 fatty acids (ω-3)] against thioacetamide (TAA)-induced liver fibrosis and clarified their underlying molecular mechanism through their effect on oxidative stress and toll-like receptor-4 (TLR-4). Forty male Wistar rats were randomized to five groups: Control group and four groups received TAA 200 mg/kg i.p. twice weekly for 8 weeks: TAA group, TAA+GL group (received GL 25 mg/kg daily by oral tube), TAA+ω-3 group (received ω-3150 mg/kg daily by oral tube), TAA+GL+ω-3 group (received similar combined doses of both natural compounds). GL, ω-3 and their combination protected the liver from TAA-hepatotoxic effects. Their hepatoprotective effects were confirmed by histopathological analysis as they significantly reduced the necroinflammatory scores and the extent of fibrosis. They act as anti-oxidant as they significantly decreased the liver malondialdehyde level (P < 0.005). They also significantly increased liver inactive TLR-4 concentration (P < 0.005) which indicates inhibition of TLR-4 pathway. This is confirmed by a significant decrease in liver TLR-4 mRNA expression (P < 0.005). In conclusion, glycyrrhizin, omega-3 fatty acids and their combination have potent anti-inflammatory, anti-oxidant and anti-fibrotic effects through inhibition of TLR-4.